2005
DOI: 10.1111/j.1651-2227.2005.tb02012.x
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of kangaroo mother care: A randomized trial of two outreach strategies

Abstract: Aim: To test whether a well‐designed educational package on the implementation of kangaroo mother care (KMC) used on its own can be as effective in implementing KMC in a healthcare facility as the combination of a visiting facilitator used in conjunction with the package. Setting: Thirty‐four hospitals in KwaZulu‐Natal Province, South Africa. Method: The hospitals were paired with respect to their geographical location and annual number of births at the facility. One hospital in each pair was randomly allocate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 10 publications
1
12
0
Order By: Relevance
“…Hospitals were paired and assigned either to receiving an evidence-based multimedia educational package on its own or to receiving on-site regional facilitation in conjunction with the use of the package. The results of the study confirmed Grimshaw et al's observation [ 1 ] – facilitation using an on-site, face-to-face strategy, combined with a carefully designed implementation package, was found to be significantly more effective than using the package on its own [ 9 ].…”
Section: Introductionsupporting
confidence: 83%
See 2 more Smart Citations
“…Hospitals were paired and assigned either to receiving an evidence-based multimedia educational package on its own or to receiving on-site regional facilitation in conjunction with the use of the package. The results of the study confirmed Grimshaw et al's observation [ 1 ] – facilitation using an on-site, face-to-face strategy, combined with a carefully designed implementation package, was found to be significantly more effective than using the package on its own [ 9 ].…”
Section: Introductionsupporting
confidence: 83%
“…The implementation of KMC was successful and the scores of Group A (on-site facilitation) were remarkably similar to the on-site facilitation scores in the Ukugona trial [ 9 ]. This confirms the assumption that face-to-face facilitation is effective in the scaling up of new health care strategies.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…6 Within the health facility, Provision of a private comfortable environment and having written protocols has also been identified as one of the supporting factors that promote KMC practice. 6,7 In Nigeria KMC was first introduced in the late 1990s through a resident pediatrician at the University of Lagos Teaching Hospital following a month-long training in Bogotá, Colombia. 8 KMC was also declared as the best option of practice in 1998 during the 29 th annual general and scientific conference of the paediatric association of Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…Where some provinces leave it to the individual hospitals to decide on the way they would implement KMC, others initiated outreaches to assist the implementation process. Some outreaches aimed at reaching all hospitals at once, such as the Ukugona Outreach in the KwaZulu‐Natal Province 18. Others, for example the Fara Ngwana Outreach in Gauteng Province and the Ukubamba Umtwana Kuwe Outreach in Mpumalanga Province, follow a staggered approach, targeting a certain number of hospitals each year 19, 20.…”
Section: Introductionmentioning
confidence: 99%